Legal evolution and convergence of rules of origin in the economic integration process of Andean Community and South American Common Market - Ortiz Valenzuela, Enio Enrique; Pinho, María Fátima (Acta Universitaria, 2015)
In Latin America the economic integration process have been slow and complex due to diversity of integrationist systems comprised with very distinctive dynamics in the region. The objective of this paperwork is to make a study about legal evolution of rules of origin as an instrument of commercial politic for market access of goods in the countries of South American Common Market (Mercosur, spanish acronim) and Andean Community (CAN, spanish acronim). This research is made through documental analysis about CAN and Mercosur related to rules of origin and their impact in sensitive sectors such as automotive industry. Between the results obtained is found that Venezuela represents factor of convergence for both schemes of integration in which could benefit the South American country, meanwhile it designs commercial strategies adapted for usage of these rules in order to impulse the development of key productive sectors for international market.